Tantangan dan Harapan Guru dalam Pendidikan Siswa Tunarungu di SLB Negeri Keleyan - Arifatul Ilmi; Nova Estu Harsiwi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study explores the challenges and expectations faced by teachers in educating deaf students at SLB Negeri Keleyan. Using a qualitative descriptive approach, data were collected through interviews and observations to understand the real experiences of teachers in the learning process. The findings reveal that one of the main challenges is teaching students with total hearing loss from birth, which demands more time, creativity, and adaptation in instructional strategies. Teachers often adjust the curriculum based on the students’ individual abilities. Despite these difficulties, students show positive development when they receive consistent encouragement, emotional support, and recognition. Teachers express hope for improved training opportunities, especially in visual and adaptive teaching techniques, as well as better support from families and the government. Additionally, they highlight the importance of assistive learning tools and inclusive job opportunities after graduation. This study affirms that with collaborative support, deaf students have the potential to grow, learn, and contribute meaningfully to society.